1986
DOI: 10.1126/science.3715453
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Secretion in Response to Cholecystokinin and Food: Differentiation of Nausea from Satiety

Abstract: Administration of cholecystokinin (CCK) to rats caused a dose-dependent increase in plasma levels of the neurohypophyseal hormone oxytocin (OT). The OT secretion was comparable to that found in response to nausea-producing chemical agents that cause learned taste aversions. The effect of CCK on OT secretion was blunted after gastric vagotomy, as was the inhibition of food intake induced by CCK. Food ingestion also led to elevated plasma OT in rats, but CCK and aversive agents caused even greater OT stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
2
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(202 citation statements)
references
References 19 publications
10
189
2
1
Order By: Relevance
“…Furthermore, preclinical data indicate that CRH may play a role in the anxiogenic (Biro et al 1993) and endocrine (Kamilaris et al 1992) effects of CCK. However, it should be noted that CCK may activate pituitary ACTH secretion, not only via CRH, but also via other neurohormones such as oxytocin and vasopressin (Carter and Lightman 1987;Verbalis et al 1986). The described association of CCK-4 induced panic attacks and an exaggerated pituitary ACTH response together with the known behavioral effects of CRH (for review see: Dunn and Berridge 1990;Holsboer et al 1992;Owens and Nemeroff 1992) are in favor of CRH mediating the panicogenic activity of CCK-4 in patients with panic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preclinical data indicate that CRH may play a role in the anxiogenic (Biro et al 1993) and endocrine (Kamilaris et al 1992) effects of CCK. However, it should be noted that CCK may activate pituitary ACTH secretion, not only via CRH, but also via other neurohormones such as oxytocin and vasopressin (Carter and Lightman 1987;Verbalis et al 1986). The described association of CCK-4 induced panic attacks and an exaggerated pituitary ACTH response together with the known behavioral effects of CRH (for review see: Dunn and Berridge 1990;Holsboer et al 1992;Owens and Nemeroff 1992) are in favor of CRH mediating the panicogenic activity of CCK-4 in patients with panic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic CCK increases pituitary hormone release via CCK-1 receptor-mediated activation of vagal afferent inputs to the caudal medulla that recruit central ascending viscerosensory pathways to the hypothalamus [43;44;45;46;47;48]. In 1986 it was reported that synthetic CCK administered peripherally at supraphysiological doses potently stimulates pituitary OT (but not AVP) secretion in rats [49]. The OT secretory responses to CCK administration were markedly attenuated after bilateral subdiaphragmatic vagotomy, after capsaicin-induced sensory vagotomy, or after systemic blockade of CCK-1 receptors [49;50].…”
Section: Viscerosensory Recruitment Of Neural Inputs To the Endocrinementioning
confidence: 99%
“…In rats, systemic CCK increases the firing rate of magnocellular OT neurons, and transiently inhibits the firing of magnocellular AVP neurons [51]. Plasma OT levels also are increased by gastric distension, which synergizes with exogenous CCK to further elevate plasma OT in rats [49]. In addition to increasing plasma OT levels, systemic CCK administration alters pituitary release of growth hormone and thyrotropin in adult male rats [52;53;54].…”
Section: Viscerosensory Recruitment Of Neural Inputs To the Endocrinementioning
confidence: 99%
“…Though the supraoptic and paraventricular nuclei themselves possess CCK receptors (Day et al, 1989;, systemically administered CCK is unlikely to access them directly, since these sites are within the blood-brain barrier. Instead CCK probably influences hormone secretion by a primary action at one of the circumventricular sites which lack an effective blood-brain barrier, or at the peripheral endings of the afferent vagus (Verbalis et al, 1986b;Carter & Lightman, 1987). Thus, it has been possible to show the induction of Fos-LI in the area postrema, a circumventricular organ, and in the dorsal vagal complex, that contains the NTS, following administration of CCK (Luckman, 1992 Luckman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%